Impact of Admission Anaemia on Short Term Outcome in Patients following Acute Ischemic Stroke - Ghosh, Ranjit Kumar; Kazi Gias Uddin Ahmed; Abu Nasir Rizvi; Priyanka Paul; Md. Masud Rana; Iftikher Alam; Rajib Das; Sahariar Hossain Siddik; Khandakar Rashed Ahmed; Md. Asaduzzaman (Bangladesh Journal of Neuroscience, 2026)
Background: Acute ischemic stroke causes a great amount of disability with economic and social burden. Therefore, prevention of stroke remains the most important means of reducing its morbidity and mortality. Effective prevention requires understanding the factors associated with the occurrence of ischemic stroke and the population subgroups at greatest risk. Reduced hemoglobin concentration has an adverse impact on the ischemic penumbra in patients with ischemic stroke as it causes reduced oxygen delivery to neuronal tissue and predisposes to infarct expansion. Aims: The purpose of this study is to evaluate the impact of admission anaemia on short term outcome in patients following acute ischemic stroke. Methods: This cross sectional study was carried out in the Department of Neurology, Dhaka Medical College and Hospital (DMCH), Dhaka for a period of two years from July 2020 to June 2022. Two hundred and seventy nine patients of acute ischemic stroke were selected consecutively through screening with set of inclusion and exclusion criteria. Each patient underwent CT of the head and/or MRI of brain and blood tests, including hemoglobin (Hb) concentration on the first day of hospitalization. Demographic, risk factor from all subjects were collected with a structured questionnaire. Neurological state of the patients was assessed on the first day of hospitalization by National Institute of Health Stroke Scale (NIHSS) and the functional status (disability) on the 1 st and 30th day after the onset of stroke by Modified Rankin Scale (MRS). After data collection analysis was done by SPSS for Windows version 26. A p value d” 0.05 was considered statistically significant. Results: Anaemia was observed more among the older patients than younger patients but there was no significant difference. Poor outcome was significantly higher in Anaemic (60.8%) than non-anaemic (39.2%) patients. Age was found significantly higher in poor outcome than good outcome (63.41±14.33 years vs 57.24±13.72 years). Admission hemoglobin was significantly lower among the patients with poor outcome both in male and female. Poor outcome was found significantly higher among male (56.6%) than female (43.4%). Anemia was found significantly higher among the patients with severe stroke (46.8%). Among anaemic patients’ mortality was significantly higher than non-anaemic patients (18.3% vs 8.2%). According to the Cox regression analysis, anaemia on admission was associated with short-term mortality in patients suffering from acute ischemic stroke [HR=2.52(95%CI: 1.18-5.36; p=0.016)]. Conclusion: Anaemia is common among patients with acute ischemic stroke and is associated with severity of stroke, unfavorable outcome and higher mortality.